2012
DOI: 10.1021/ma300314q
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Functional Copolymers with Blocky Architectures via Carbene Polymerization

Abstract: We present our results obtained in the Rh-catalyzed carbene copolymerization of diazomethane and diazoesters as a new approach to functional polymer synthesis. Copolymerization reactions were successful, and high-M w ethylene–acrylate type copolymers were obtained with a large variation in functional group content, which proved to be tunable by varying the monomer feed ratio and the way of addition. Polymer yields decrease strongly with increasing incorporation of diazomethane due to rapid β-hydride eliminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 56 publications
0
30
0
Order By: Relevance
“…268,270 The M w of the polymers can be tuned by varying the Rh catalyst and the polymerisation conditions. 268 Recently, it was shown that these Rh catalysts are also able to copolymerise functionalised carbenes with non-functionalised carbenes generated from either diazomethane 271 or sulfoxonium ylides 272 copolymers exhibit a blocky microstructure and the functionalgroup content can be tuned in a large window by varying the feed ratio of the two monomers. Copolymerisation of functionalised carbenes with ethene is also possible, albeit leading to quite inhomogeneous polymer mixtures.…”
Section: Scheme 49 Migratory Insertion Of Carbenesmentioning
confidence: 99%
“…268,270 The M w of the polymers can be tuned by varying the Rh catalyst and the polymerisation conditions. 268 Recently, it was shown that these Rh catalysts are also able to copolymerise functionalised carbenes with non-functionalised carbenes generated from either diazomethane 271 or sulfoxonium ylides 272 copolymers exhibit a blocky microstructure and the functionalgroup content can be tuned in a large window by varying the feed ratio of the two monomers. Copolymerisation of functionalised carbenes with ethene is also possible, albeit leading to quite inhomogeneous polymer mixtures.…”
Section: Scheme 49 Migratory Insertion Of Carbenesmentioning
confidence: 99%
“…De Bruin and co-workers showed that functionalised and nonfunctionalised carbenes formed from either diazomethane or sulfoxonium ylides could be copolymerised using these rhodium catalysts, with the resulting copolymers exhibiting a blocky microstructure (Figure 18). 98,99 The composition and thus also the functional group content could be tuned by varying the monomer feed ratio over a large range.…”
Section: C1 Polymerisationmentioning
confidence: 99%
“…Please do not adjust margins Figure 18: Copolymerisation of functionalised carbenes using rhodium catalysts. 98,99 Ma and co-workers 100 described the preparation of a hydroxyl-terminated poly(methylene) via polyhomologation of dimethylsulfoxonium ylides and oxidation, and these and related polymers were employed in a similar manner to that shown in Figure 7 to make block polymers via ATRP, 101,102 or ring-opening polymers. 103 In the last few years, Hadjichristidis and co-workers 104 described the one-pot combination of polyhomologation and living anionic polymerisation to produce PE block copolymers.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Recently we have shown that copolymers of functionalised and non-functionalised carbenes (thus exhibiting similar structures to copolymers of carbenes and ethene) showed indeed unique material properties, thereby emphasizing the potential of this approach. 52,53 However, these copolymerisations required the use of diazomethane or dimethylsulfoxonium ylides, which limits the application of this process significantly. In this respect, extending this concept to the use of ethene would be beneficial.…”
Section: Dalton Transactions Papermentioning
confidence: 99%